BRAIN-LUNG-THYROID SYNDROME - M. A. Belyashova; D. Yu. Ovsyannikov (Union of pediatricians of Russia, 2014)
Brain-lung-thyroid syndrome is a rare genetic disease characterized by pathology of the syndrome affected organs. This syndrome is based on mutations of the NKX2-1 gene, which encodes the thyroid transcription factor. Clinical manifestation of brain-lung-thyroid syndrome is characterized by a variable phenotype. The article presents the first Russian clinical observation of a patient with a genetically confirmed disease. Combination of such symptoms as motor development delay, ataxia, muscular hypotonia, recurrent lower airway infections, hypothyroidism helped to assume and then confirm brain-lung-thyroid syndrome by means of genetic analysis. The article also presents world literature findings (1998-2014) on clinical observations of this disease in respect of genetics, pathogenesis, pathomorphology, clinical pattern and therapy.